The Implementation of â€˜Good Governanceâ€™ in the Placement Process of Indonesian Migrant Domestic Workers - Mindarti, Lely Indah (International Journal of Social and Local Economic Governance, 2015)
A research about â€˜good governanceâ€™ implementation of Indonesian Women Worker- housemaid ( in Indonesia TKI-PRT) placement process, focused on the transparency application issue to develop the governance of online information management system of TKI-PRT placement process. The main issues being examined were such as whether the substance of laws and regulations and practices applied in the migrant workers placement process is relevant so far to the need for developing online information management system to become more transparent and may strengthen protective support to TKI-PRT. The research was in the form of case study and analyzed by using content analysis technique.Protection to TKI-PRT, as it is defined in the Law No. 39/2004 that â€œthe first and best opportunity of protection should arise from the workers themselvesâ€. The implication, strengthening transparency and protection of TKI are by nature urgent and require the development of information management system governance of TKI placement based on self-governance model. One governance model with citizen centricity character grows through the mechanism of governance from the ground-up, closely focused and centralized based on the continuous strengthening of the TKI-PRT autonomous capacity to be more proactive to become active agent of change, especially as an active evaluator and creator of information in the whole implementation process of migrant worker placement abroad. The autonomous capacity of these TKI is likely collective created, meaning the success depends on the commitment of all stakeholders who are synergic proliferating and strengthening the autonomy and integrity of all actor practices. In particular, they should conduct â€˜tri-automizationâ€™ of TKI independence and self-reliance in terms of cultural, economic and political aspects. Based on the result of the research, it can be summarized that the substance of the management and implementation of TKI placement process in Malaysia so far is likely bureaucrtaic centricity rather than citizen centricity. It was indicated by seven dominant tendencies which made transparency and protection functions not effective and even may cause TKI-PRT vulnerability potential in all stages of the placement implementation processes abroad. Therefore, renewal of the regulations substance about TKI-PRT placement process, including the information management system, is really urgent. The regulations and impelementation substance should be consistent and rely on the need of the emancipatory information management system development, in the form of self-governance model which is to urge the government as enabler to the strengthening and institutionalizing the autonomy and integrity of all actor practices.